SIGNIFICANCE OF CRIMINOLOGICAL RESEARCH IN TOURISM DEVELOPMENT - Badzagua, Malkhaz; Badzagua, Mikheil (European Scientific Journal, ESJ, 2015)
Despite the world economic crisis, Georgia is rapidly developing tourism industry. In this regard, while planning new tourist projects, forecasting crime and its seasonal variations is as important as weather forecasting. In relatively short period of time, in particular small tourist area lots of visitors are brought together what automatically means the increase of the danger of crime and thus, requires adequate and coordinated response from the state and society. The Analytical Department at the Ministry of Internal Affairs of Georgia, in 2011, delivered a statistical report “foreign visitors and crime in Georgia" which showed that along with tourism development, grew crimes committed against and by tourists and there was a significant seasonal factor. Carrying out criminological researches for good planning tourism will enable society and the state structures to effectively perform their basic function - crime prevention. For this purpose, we recommend under the Ministry of Internal Affairs, to create Criminological Research Center.